RADLOF, Frans Gustav Theodor Inventory of documents - RADLOF, Frans Gustav Theodor (ARCA, 2018)
Private papers of F.G.T. Radlof, General manager Banana Control Board [1958-1968], Manager in ARMSCOR and Editor of SALVO, SA Association of Industrial Editors [SAAIE], Communicator of the Year in 1977.
COVERAGE 1976-1992; 198 Files; 4.22 metre
Keywords: RADLOF, Frans Gustav Theodor; Inventories